(untitled) - Dorling Kindersley, Inc. (New York, NY, 2005)
In just 15 minutes a day you can speak and understand German with confidence. Unique visual approach makes learning quick, easy and fun. No writing or homework - just use the cover flaps to hide the answers and test yourself as you learn.
Keywords: German language,Ngôn ngữ Đức; Study and teaching,Học và dạy